1982
DOI: 10.1017/s0021859600041289
|View full text |Cite
|
Sign up to set email alerts
|

The effects of light illuminance and wavelength on the growth of broiler chickens

Abstract: The effects of light illuminance and wavelength on the growth of male and female broiler chickens from day-old to 8 weeks of age were studied. Different coloured lights, at equal illuminance and peak wavelengths of 425, 525 and 610 nm and a broad-spectrum white light of median wavelength 560 nm had no significant effect on the growth rate or cumulative food intake of birds of either sex.The performance of male broilers was unaffected by light of different illuminances, equal to 0-7, 3-0, 15-0 and 46-5 lux. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
4
13
0
Order By: Relevance
“…It is unlikely that variations in the spectral distribution of the various light sources influence growth and food conversion, despite the significant, though inconsistent, differences reported by Zimmermann (1988) in body weight and FCR among birds grown under a variety of light sources which varied in spectral characteristics. Similar body weights and food intakes were reported for broilers reared under blue, green, red or white fluorescent tubes to 56 days of age by Source (intensity -1x)t Findings Andrews and Zimmermann (1990) Cherry and Barwick (1962) Hulan and Proudfoot (1987) Proudfoot and Hulan (1987) Scheideler (1990) Wabeck and Skoglund (1974) Wathes et al (1982) Zimmermann (1988) CoF (7); CiF (12) Wathes et al (1982), and minimal differences were observed in broilers grown under blue, green, red, yellow fluorescent tubes or incandescent lamps to 63 days of age by Wabeck and Skoglund (1974). Whilst light source does not appear to influence mortality, it may have an effect on the incidence of certain skeletal abnormalities.…”
Section: Production Responses Broilerssupporting
confidence: 54%
“…It is unlikely that variations in the spectral distribution of the various light sources influence growth and food conversion, despite the significant, though inconsistent, differences reported by Zimmermann (1988) in body weight and FCR among birds grown under a variety of light sources which varied in spectral characteristics. Similar body weights and food intakes were reported for broilers reared under blue, green, red or white fluorescent tubes to 56 days of age by Source (intensity -1x)t Findings Andrews and Zimmermann (1990) Cherry and Barwick (1962) Hulan and Proudfoot (1987) Proudfoot and Hulan (1987) Scheideler (1990) Wabeck and Skoglund (1974) Wathes et al (1982) Zimmermann (1988) CoF (7); CiF (12) Wathes et al (1982), and minimal differences were observed in broilers grown under blue, green, red, yellow fluorescent tubes or incandescent lamps to 63 days of age by Wabeck and Skoglund (1974). Whilst light source does not appear to influence mortality, it may have an effect on the incidence of certain skeletal abnormalities.…”
Section: Production Responses Broilerssupporting
confidence: 54%
“…When different lighting intensities ranging from 0.7 to 46.5 lux were compared, Wathes et al (1982) observed no significant effects on male broiler growth and feed intake, although the weight gain of females was depressed at light intensities above 3 lux. Newberry et al (1986) found no differences in body weight, mortality or leg disorders between male broilers reared under lighting intensities ranging from 0.5 to 100 lux.…”
Section: Light Intensitymentioning
confidence: 87%
“…However, according to the reports of Wathes et al (1982) and Newberry et al (1986), light intensity was within desirable ranges during each trial for all of the light sources (1.6 to 20 lx). Thus, there is no indication of a light intensity effect on broiler performance in the field trials reported herein.…”
Section: Resultsmentioning
confidence: 85%
“…Wabeck and Skoglund (1974) reported increased weight gain in broilers raised under blue or green fluorescent lamps versus red or white incandescent bulbs without any effect on feed conversion or mortality. Wathes et al (1982) reported no differences in growth rate or feed conversion in either males or females grown under blue, green, red, or white light. Zimmermann (1988) most recently reported increased 48-day broiler weights with warm white and compact fluorescent lamps compared to incandescent lamps.…”
Section: Introductionmentioning
confidence: 93%